1980
DOI: 10.1038/284616a0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of high molecular weight forms of ACTH on the fetal sheep adrenal

Abstract: The direct involvement of the pituitary-adrenal axis in birth has been well established, at least in sheep, and its removal prolongs pregnancy. As part of the process the fetal sheep adrenal grows rapidly during the 10-15 d prepartum and is associated with a large rise in the plasma corticosteroid concentration. This does not seem to result from an increased ACTH secretion. The fetal adrenal in vivo seems refractory to circulating ACTH and shows poor response to elevation of plasma concentration. Thus the sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…In support of this proposal, adrenal cells from 120-day-old fetuses, maintained in an ACTH-free medium, exhibit enhanced responsiveness as the time in culture increases, suggesting the existence of an inhibitor of ACTH action in vivo (Durand et al 1982). It has been suggested that these putative inhibitory factors are the high molecular weight (HMW) precursor peptides of ACTH itself, since these peptides have been shown to inhibit ACTH-induced cortisol secretion from adrenal cells in vitro (Roebuck et al 1980, Jones et al 1992. As the HMW ACTH-containing peptides are present in fetal plasma in high concentrations (Saphier et al 1993, Carr et al 1995, recent attention has therefore focused on the ratio of low molecular weight (LMW) to HMW ACTH, since it has been proposed that the balance between the stimulatory action of ACTH and the proposed inhibitory action of the HMW ACTH precursor peptides is involved in the regulation of fetal adrenal responsiveness and basal cortisol secretion (Roebuck et al 1980, Durand et al 1982.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In support of this proposal, adrenal cells from 120-day-old fetuses, maintained in an ACTH-free medium, exhibit enhanced responsiveness as the time in culture increases, suggesting the existence of an inhibitor of ACTH action in vivo (Durand et al 1982). It has been suggested that these putative inhibitory factors are the high molecular weight (HMW) precursor peptides of ACTH itself, since these peptides have been shown to inhibit ACTH-induced cortisol secretion from adrenal cells in vitro (Roebuck et al 1980, Jones et al 1992. As the HMW ACTH-containing peptides are present in fetal plasma in high concentrations (Saphier et al 1993, Carr et al 1995, recent attention has therefore focused on the ratio of low molecular weight (LMW) to HMW ACTH, since it has been proposed that the balance between the stimulatory action of ACTH and the proposed inhibitory action of the HMW ACTH precursor peptides is involved in the regulation of fetal adrenal responsiveness and basal cortisol secretion (Roebuck et al 1980, Durand et al 1982.…”
Section: Introductionmentioning
confidence: 97%
“…In vitro and in vivo studies have shown that the fetal adrenal gland becomes increasingly responsive to ACTH stimulation in the last few weeks of gestation (Wintour et al 1975, Jones et al 1977, Glickman & Challis 1980, Rose et al 1982. Jones & Roebuck (1980) suggested that the ability of the ovine fetal adrenal gland to respond to circulating ACTH in vivo was suppressed by some factor(s), since they found a discrepancy between adrenal cortisol responses to ACTH in vitro and in vivo. In support of this proposal, adrenal cells from 120-day-old fetuses, maintained in an ACTH-free medium, exhibit enhanced responsiveness as the time in culture increases, suggesting the existence of an inhibitor of ACTH action in vivo (Durand et al 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gasson (1979) (Roebuck et al, 1984). The inhibition of ACTH 1-39 bioactivity by macromolecular forms could be related to the presence in their molecule of the 15-18 ACTH sequence which, by occupying corticotropin membrane receptors might prevent ACTH 1-39 from exercising its corticosteroidogenic activity (Hofmann, 1974in Roebuck et al, 1980. According to Gasson (1979) Dupouy, 1980b), it is possible that these drastic changes in adrenal activity are related to the evolution of the different molecular forms of ACTH during the perinatal period.…”
Section: Discussionmentioning
confidence: 99%
“…1) Three immunoreactive forms of ACTH are characterized by their apparent molecular weight (MW) (Orth et al, 1970(Orth et al, , 1973 (Eipper and Mains, 1978 ;Mains and Eipper, 1979) which also contains the amino acid sequences of both the /3LPH and 16-K fragments located near the N-end of the precursor (Lowry et al, 1976 ;Eipper and Mains, 1978 ;Nakanishi et al, 1979 Dupouy, 1980b (Dupouy, 1976 in the pituitary gland of the sheep fetus and the lamb which contains abundant material of high molecular weight (Silman, 1979 ;Silman et al, 1979 ;Roebuck et al, 1980 (Silman et al, 1978).…”
Section: Discussionmentioning
confidence: 99%